Protocol for the POMELO (Prevention Of MusclE Loss in Osteoarthritis) randomized pilot feasibility trial. Issue 4 (December 2022) - Godziuk, Kristine; Prado, Carla M; Forhan, Mary
Abstract: Objective: Individuals with advanced knee osteoarthritis (OA) and a large body size [a body mass index (BMI) ≥35 ​kg/m 2 ] have a higher risk of complications with total knee arthroplasty (TKA), and hence may be ineligible for surgery unless they reduce their BMI. However, pre-TKA weight-loss has not been shown to reduce surgical infection risk and may inadvertently increase risk for muscle loss and development of sarcopenic obesity (low muscle and low strength with higher fat mass). This suggests that a knee OA management approach that doesn't focus on weight change (weight-neutral) may be beneficial. This study examines if a weight-neutral behavioural intervention is feasible and acceptable to participants, and improves muscle mass and physical function in comparison to usual care. Design: This pilot randomized clinical trial compares a 12-week multimodal intervention [including targeted nutrition, progressive resistance exercise, and arthritis self-management support] to usual care. Co-primary outcomes are feasibility and acceptability, with secondary outcomes of change in lean soft tissue and physical function within and between groups at 3-months and 9-months from baseline. Change in waist circumference, fat mass, blood biomarkers, energy metabolism, OA-related pain and function, health-related quality of life, self-efficacy for arthritis management, and interest in pursuing a TKA within and between groups will be explored. Conclusion: This study will inform future development of more personalized knee OA treatment approaches for adults with larger bodies. Further, this will contribute to effective alternative treatment pathways that reduce inequities in access to OA care for this understudied patient population.